In Praise of Eclecticism: Relational Thinking and Theoretical Assemblage - Monson, Ingrid (Current Musicology, 2018)
In this essay I trace a path through the intellectual history of the last thirty-five years by using the idea of relationality to connect widely different theoretical frameworks that have been used in the fields of ethnomusicology and musicology. These perspectives are all part of a generalized move away from the fixity of structuralism and towards more contingent, dynamic, and anti-foundationalist modes of understanding power, identity, embodiment, technology, and the sensory. Although philosophical perspectives must be addressed, I am fundamentally more interested in exploring the application of these ideas to empirical work—historical and ethnographic. To this end I sing in praise of theoretical eclecticism: the practice of selecting the most productive ideas from philosophy, social theory, and other fields, according to how well they can illuminate and frame an empirical project. To borrow a concept from a recently fashionable philosopher, I suggest that creating theoretical assemblages with clear points of connection to the principle topic of research might serve us well. Deleuze famously advocated for a rhizomatic rather than arborescent understanding of interconnection: “unlike trees or their roots, the rhizome connects any point to any other point, and its traits are not necessarily linked to traits of the same nature; it brings into play very different regimes of signs, and even nonsign states” (Deleuze and Guattari 1987, 21). Or more pithily: “We’re tired of trees. We should stop believing in trees, roots, and radicles. They’ve made us suffer too much” (15). Assemblages, for Deleuze and Guattari, are non-hierarchical consistencies that develop among these connections and they may link different strata. After tracing an outline of the legacy of relational thinking I will show how and why I have applied an anthropological assemblage theory of ethics and morality to my work on Malian balafonist Neba Solo in conjunction with older social and cultural theories. This essay also addresses the limits of Deleuze and Guattari’s concept of assemblage, and philosophical perspectives more generally, as resources for socially engaged empirical musical studies. The need to engage issues of power, inequality, diversity and gender inequality, I argue, requires engagement with the social sciences, such as sociology, anthropology, and economics. Emphasis on these social theoretical resources encapsulates one historical difference between musicology and ethnomusicology in terms of relational thinking.